Assessment of the quality of the examination in pharmacy curriculum - Khin Soe, May; Abdul Razak, Tariq; Mohd Noor, Noriah; Ahmad Rusmili, Muhamad Rusdi (2011)
The Faculty of Pharmacy, International Islamic University Malaysia conducted this survey during the second semester examination in March-April 2007 in order to improve and upgrade the quality of examination in pharmacy education. This study attempted to assess the perception of students on the duration of the exam, clarity of exam questions, difficulties of subjects, discrimination between weak and good students and their expected grading. Moreover, relevance and the applicability of the courses offered by Basic Medical Sciences Department were investigated. Cross sectional descriptive study was conducted. Questionnaires were distributed to 159 students in the examination hall after an examination. All targeted students responded to the questionnaires. The students were asked to comment on the examination, lecturers and course out lines. All information was recorded for further consideration in the next curriculum review. SPSS was used to analyze the data and chi-square test for goodness of fit was done to compare categorical variables. The actual grade and expected grade was compared statistically. It was observed that 51% of students did not have sufficient time to completely answer the “Pharmacology of Periphery Nervous System” paper. Among other subjects, common MCQ was said to be not easily understandable. Questions on “Sensory System” paper was said to be the least relevant within the course objectives. “Cardiovascular and Respiratory system” papers were found to be the most discriminative subjects. It was observed that “Common MCQ” was the most difficult than others. However, 59.6% of students expected that they could get A or A- in Microbiology paper. The grading expected by the students and actual grading marked by the lecturers was found to be different but it was not statistically significant (p>0.05). The finding of this study was reviewed to make recommendation on measures to improve the curriculum and learning outcomes. Key Words: Perception of Examination, Pharmacy student, Basic medical Sciences Subjects